OXIDATION STATE AND COORDINATION OF FE IN MINERALS: AN FE K-XANES SPECTROSCOPIC STUDY - Wilke M.; Farges F.; Petit P.-E.; Brown G.E.; Martin F. (My University, 2001)
High-resolution Fe K-edge XANES spectra of a series of crystalline Fe2+- and Fe3+-bearing model compounds were measured in an effort to correlate characteristics of the pre-edge feature with oxidation state and local coordination environment of Fe atoms. The model compounds comprise 30 natural minerals and synthetic compounds, with Fe coordination environments ranging from 4 to 12 O atoms for Fe2+, including 5-coordinated trigonal bipyramidal Fe2+, and from 4 to 6 O atoms For Fe3+. Most pre-edge spectra show two components (due to crystal-field splitting) that are located just above the Fermi level. The most useful characteristics of the Fe-K pre-edge for determining Fe oxidation state and coordination number are the position of its centroid and its integrated intensity. The separation between the average pre-edge centroid positions for Fe2+ and Fe3+ is 1.4 +/- 0.1 eV. Thus, the position of the pre-edge feature can be used as a measure of the average Fe-redox state, with the average pre edge position for mixed Fe2+-Fe3+ compounds occurring between positions for Fe2+ and Fe3+. The lowest pre-edge normalized heights and integrated intensities are observed for the most centrosymmetric sites of Fe, in agreement with previous studies (see Waychunas et al. 1983). Examination of the pre-edge features of mechanical mixtures of phases containing different proportions of Fe2+ and Fe3+ suggests that the pre-edge position and intensity for these mixtures can vary quite non-linearly with the average redox state of Fe. However, distinctly different trends of pre-edge position vs, pre-edge intensity can be observed, depending on the coordination environment of Fe2+ and Fe3+, with an accuracy in redox determination of +/- 10 mol% provided that the site geometry for each redox state is known. These methods have been used to estimate the Fe3+/Fe2+ ratio in 12 minerals (magnetite, vesuvianite, franklinite, rhodonite, etc.) containing variable/unknown amounts of Fe2+/Fe3+.